Systemic bile acid sensing by G protein‐coupled bile acid receptor 1 (GPBAR1) promotes PYY and GLP‐1 release. (16th May 2013) - Ullmer, C; Alvarez Sanchez, R; Sprecher, U; Raab, S; Mattei, P; Dehmlow, H; Sewing, S; Iglesias, A; Beauchamp, J; Conde‐Knape, K
<x xml:space="preserve">Abstract</x> Background and Purpose Nutrient sensing in the gut is believed to be accomplished through activation of GPCRs expressed on enteroendocrine cells. In particular, L‐cells located predominantly in distal regions of the gut secrete glucagon‐like peptide 1 (GLP‐1) and peptide tyrosine‐tyrosine (PYY) upon stimulation by nutrients and bile acids (BA). The study was designed to address the mechanism of hormone secretion in L‐cells stimulated by the BA receptor G protein‐coupled bile acid receptor 1 (GPBAR1). Experimental Approach A novel, selective, orally bioavailable, and potent GPBAR1 agonist, RO5527239, was synthesized in order to investigate L‐cell secretion in vitro and in vivo in mice and monkey. In analogy to BA, RO5527239 was conjugated with taurine to reduce p.o. bioavailability yet retaining its potency. Using RO5527239 and tauro‐RO5527239, the acute secretion effects on L‐cells were addressed via different routes of administration. Key Results GPBAR1 signalling triggers the co‐secretion of PYY and GLP‐1, and leads to improved glucose tolerance. The strong correlation of plasma drug exposure and plasma PYY levels suggests activation of GPBAR1 from systemically accessible compartments. In contrast to the orally bioavailable agonist RO5527239, we show that tauro‐RO5527239 triggers PYY release only when applied intravenously. Compared to mice, a slower and more sustained PYY secretion was observed in monkeys. Conclusion and Implications Selective GPBAR1 activation elicits a strong secretagogue effect on L‐cells, which primarily requires systemic exposure. We suggest that GPBAR1 is a key player in the intestinal proximal‐distal loop that mediates the early phase of nutrient‐evoked L‐cell secretion effects.